Features of ophiolite movement in the Baluran- Al-Zaytouna- Beit Al-Qusayr sites (Latakia University Journal -Basic Sciences Series, 2024)
This research presents a petrographic study of the rocks of the ophiolitic complex at the sites of Baloran Al-Zaytouna and Beit Al-Qasir Which is located in northwestern Syria, northwest of the city of Latakia.This research aims to clarify the movement of ophiolites over the sites of Baloran, Al-Zaytouna, and Beit Al-Qasir, and to determine the distance of the ophiolite blocks from each other.Field tours were carried out, geological sections were uploaded, and rock slides were studied to interpret the movement of ophiolites in the studied sites, as the Baloran area is considered a dividing line between ophiolite rocks and carbonate rocks (south-eastern border) Where the ophiolite begins directly at the Baloran Dam, represented by the upper pillow lava (the upper part of the ophiolite The absence of the lower pillow lava, Followed by rocks of the volcanic-sedimentary formation represented by radiolarite and colored marly clay layers on the western end of the Bluran Dam, with the absence of limestone rock and breccia. Gabbro-dolorite clasts (the central part of the ophiolite) appear near the village of Zaytouna-Beit Qusayr, and this indicates a divergent systematic placement as a result of thrusting processes towards the southeast, where the pillow lava and radiolarite diverged from the gabbro-dolorite clasts by a distance of more than 1000 m.